Quantitative Assessment of Passive Load Balancing for a Designed HVAC Installation: Case study in Magnificent Hall, Deli Park - S Suparmono; C Cholish; A Abdullah; Sinambela, Haksa; Alda, Tania; Matondang, Aprima A.; Simanjuntak, Andrean V. (UIR PRESS, 2025)
This study presents a comprehensive analysis of a designed three-phase electrical distribution system for a dedicated Heating, Ventilation, and Air Conditioning (HVAC) plant. Based on data extracted from a single-line diagram and load schedule, a significant inherent load imbalance of 9.15% was identified. This paper outlines a four-stage methodology to investigate the consequences and propose a solution. The methodology includes a system audit, simulation-based consequence analysis of energy losses and motor derating, design of a no-cost phase-swapping mitigation strategy, and a techno-economic evaluation. The proposed passive balancing reduces the load imbalance to 1.32%. The study highlights the critical importance of meticulous load scheduling during the initial design phase to enhance system efficiency, ensure equipment longevity, and achieve significant operational cost savings without capital expenditure.